Enabling security for service discovery in pervasive computing environments - Sharifi, Mahdi (2009)
Nowadays, the digital world is witnessing the birth of a revolutionary computing paradigm that promises to have a profound effect on the way users interact with computers, devices, physical spaces, and other users. Pervasive or ubiquitous computing is a new technology introduced to computer science and digital world and has been investigated since 1993. Since the beginning of the new millennium, this concept has been actualized more than in the past and became more realistic than a dream. Making the computer disappear from the eyes of the people, in a way that people cannot feel the presence of computers is the other aim of pervasive computing. In a broad sense, pervasive computing includes four major areas: mobile computing, wireless networks, embedded computing and context-aware sensor networks. Furthermore, the presence of service discovery in pervasive environments is an unavoidable principle considering the fact that the number of available services is increasing on the fly in such environments. Meanwhile, providing security for processes in pervasive computing environments to maintain communicating information securely and reliable is a demanding task. This study aims to analyze security requirements raised in service discovery in pervasive computing environments and proposes a secure framework to enable service discovery to adapt with security issues, in particular authentication, in pervasive computing environments in order to obtain secure pervasive computing envisions. Moreover, in order to demonstrate the proposed framework design, the prototype applying a case study is illustrated.